Strategies to Improve Health Care Services - Kirillova, Larisa Konstantinovna (International Review of Management and Marketing, 2016)
reforms in Russia. We consider the economic substance of healthcare services, the specificity of their provision. Reveals social peculiarity of medical services and a high significance for national security. Based on existing publications spent a comparative analysis of healthcare reform in foreign countries. Generalized health financing mechanisms used by national governments. Disclose concept combining paid and free medical services. The paper presents the market mechanism to provide health care services. Represented the results of the introduction of market reforms in the healthcare of Russia. Analyzes the performance evaluation of the effectiveness of medical services, offers internal and external criteria for the evaluation of medical to improve the availability and quality of medical care. Represented the method of evaluating the effectiveness of medical practice. Grounded the necessity of expanding the volume of paid medical services for compensation of public financial resources. Proposed the conditions for the introduction of paid services in the health care system. Keywords: Affordability of medical services; Economic efficiency; Efficiency of health care; Health care services; Paid medical services; Quality of medical services. JEL Classification: I1